Radiolabeled Anti-Adenosine Triphosphate Synthase Monoclonal Antibody as a Theragnostic Agent Targeting Angiogenesis - Bok-Nam Park PhD; Su Jin Lee MD, PhD; Jung Hyun Roh MS; Kyung-Han Lee MD, PhD; Young-Sil An MD, PhD; Joon-Kee Yoon MD, PhD (Molecular Imaging)
Introduction: The potential of a radioiodine-labeled, anti-adenosine triphosphate synthase monoclonal antibody (ATPS mAb) as a theragnostic agent for simultaneous cancer imaging and treatment was evaluated. Methods: Adenosine triphosphate synthase monoclonal antibody was labeled with radioiodine, then radiotracer uptake was measured in 6 different cancer cell lines. In vivo biodistribution was evaluated 24 and 48 hours after intravenous injection of 125 I-ATPS mAb into MKN-45 tumor-bearing mice (n = 3). For radioimmunotherapy, 18.5 MBq 131 I-ATPS mAb (n = 7), isotype immunoglobulin G (IgG) (n = 6), and vehicle (n = 6) were injected into MKN-45 tumor-bearing mice for 4 weeks, and tumor volume and percentage of tumor growth inhibition (TGI) were compared each week. Results: MKN-45 cells showed the highest in vitro cellular binding after 4 hours (0.00324 ± 0.00013%/μg), which was significantly inhibited by unlabeled ATPS mAb at concentrations of greater than 0.4 μM. The in vitro retention rate of 125 I-ATPS mAb in MKN-45 cells was 64.1% ± 1.0% at 60 minutes. The highest tumor uptake of 125 I-ATPS mAb in MKN-45 tumor-bearing mice was achieved 24 hours after injection (6.26% ± 0.47% injected dose [ID]/g), whereas tumor to muscle and tumor to blood ratios peaked at 48 hours. The 24-hour tumor uptake decreased to 3.43% ± 0.85% ID/g by blocking with unlabeled ATPS mAb. After 4 weeks of treatment, mice receiving 131 I-ATPS mAb had significantly smaller tumors (679.4 ± 232.3 mm 3 ) compared with control (1687.6 ± 420.4 mm 3 , P = .0431) and IgG-treated mice (2870.2 ± 484.1 mm 3 , P = .0010). The percentage of TGI of 131 I-ATPS mAb was greater than 50% during the entire study period (range: 53.7%-75.9%). Conclusion: The specific binding and antitumor effects of radioiodinated ATPS mAb were confirmed in in vitro and in vivo models of stomach cancer.